The Working with Parents in Sport Model (WWPS-Model): A practical guide for practitioners working with parents of elite young performers - Lafferty, M. E.; Triggs, C. (Journal of Sport Psychology in Action, 2014)
In this article we introduce the Working with Parents in Sport Model (WWPS-Model), which highlights key areas applied practitioners can use to inform their practice with regard to the development and implementation of support programs for parents/guardians of elite junior athletes. The stage approach and nature of the model, which is accompanied by practical checklists, are all intended to serve as a valuable resource to both the experienced professional and the neophyte practitioner about to engage on the applied practice journey within an elite junior sporting environment.